Articular compromise after chikungunya fever in a second tier hospital during the 2015 epidemic. Asunción, Paraguay - Jhonatan Losanto; Susan Riquelme-Granada; Yanira Yinde; Margarita Duarte; Francisco Giménez; Aldo Ojeda (Sociedad Paraguaya de Reumatología, 2017)
Introduction: Chikungunya fever is a viral disease caused by an alphavirus from the Togaviridae family, that is transmitted by mosquitoes of the genus Aedes. It is manifested by fever, skin rash and joint pain. A high percentage of patients develop a persistent polyarthritis that can last for months or even years. Objectives: To describe the clinical and epidemiological characteristics of patients diagnosed with arthritis after Chikungunya fever. Materials and methods: A retrospective, cross-sectional study of patients who were seen at the District Hospital of Villa Elisa during the first semester of 2015, and were diagnosed with Chikungunya fever. Results: A total of 26 patients from Asunción were included, of which 92% were women, with an average age of 47.2 years. The predominant symptoms were arthralgia (92.3%) and headache (76.9%). Joint symptoms started on average 14 days after the onset of fever. The proximal metacarpophalangeal and interphalangeal joints were affected in 73% of the patients, the radiocarpal and knee joints in 76.9%, shoulders in 50% and feet in 92.3%. All patients were treated with NSAIDs and 76.9% received treatment with prednisone, with partial or total improvement of symptoms in 92.3% of the cases. Two patients (7.6%) required Methotrexate due to the persistence of arthritis after corticosteroids were discontinued. Conclusion: Chikungunya fever is a major health issue in our country, especially due to its ability to generate rheumatological complications in the medium and long run. We must pay special attention to this pathology since the chronic joint compromise can lead to disability and labor absenteeism, which would translate into overload of the public health system.